2015
DOI: 10.1530/joe-15-0099
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase 4 inhibitor improves brain insulin sensitivity, but fails to prevent cognitive impairment in orchiectomy obese rats

Abstract: It is unclear whether the dipeptidyl peptidase 4 (DPP4) inhibitor can counteract brain insulin resistance, brain mitochondrial dysfunction, impairment of hippocampal synaptic plasticity and cognitive decline in testosterone-deprived obese rats. We hypothesized that DPP4 inhibitor vildagliptin improves cognitive function in testosterone-deprived obese rats by restoring brain insulin sensitivity, brain mitochondrial function and hippocampal synaptic plasticity. Thirty male Wistar rats received either a sham-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…17 Several studies showed that orchiectomized rodents developed the impairment of learning and memory. 18 Although our previous studies demonstrated that in testosterone-deprived rats, obesity did not aggravate the cognitive impairment in orchiectomized rats; 6,25,26 it was not clear whether obesity occurred too late to aggravate the already impaired cognition by testosterone deprivation. [22][23][24] In addition, testosterone replacement in orchiectomized rats increased synaptic plasticity and increased learning and memory processes.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…17 Several studies showed that orchiectomized rodents developed the impairment of learning and memory. 18 Although our previous studies demonstrated that in testosterone-deprived rats, obesity did not aggravate the cognitive impairment in orchiectomized rats; 6,25,26 it was not clear whether obesity occurred too late to aggravate the already impaired cognition by testosterone deprivation. [22][23][24] In addition, testosterone replacement in orchiectomized rats increased synaptic plasticity and increased learning and memory processes.…”
mentioning
confidence: 92%
“…[22][23][24] In addition, testosterone replacement in orchiectomized rats increased synaptic plasticity and increased learning and memory processes. 18 Although our previous studies demonstrated that in testosterone-deprived rats, obesity did not aggravate the cognitive impairment in orchiectomized rats; 6,25,26 it was not clear whether obesity occurred too late to aggravate the already impaired cognition by testosterone deprivation. Moreover, the roles of microglia and astrocyte function, hippocampal and cortical oxidative stress, and hippocampal and cortical apoptosis have never been investigated in obese-insulin resistance with testosterone-deprived model.…”
mentioning
confidence: 92%
“…A dipeptidyl peptidase-4 (DPP-4) inhibitor, vildagliptin, has been shown to improve both peripheral insulin resistance and LV function in a similar manner to the physiological dose of TRT without any changes in plasma testosterone levels in orchiectomized rats with obese insulin resistance (Pongkan et al 2016). On the other hand, vildagliptin failed to prevent the cognitive impairment in those rats (Pintana et al 2015). Thus, a combined low-dose TRT with vildagliptin may provide a great benefit in the treatment of obese subjects with testosterone deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…The HOMA (Homeostasis Model Assessment) was required to evaluate the severity of insulin resistance. The higher the HOMA index was taken as indicating the severity of insulin resistance at periphery (Pipatpiboon et al 2012, Pintana et al 2015b, Pratchayasakul et al 2015.…”
Section: The Determination Of Metabolic Parameters By Chemical Analysismentioning
confidence: 99%
“…Despite an important role in promoting secondary sexual characteristics in males (Schiavi & White 1976), testosterone also plays a significant role in cognition (Hogervorst et al 2001, Kenny et al 2004, Pintana et al 2015a). It has been reported that testosterone deficiency, caused by orchiectomy, resulted in insulin resistance in periphery (Grossmann et al 2008, Xia et al 2013, subsequently resulting in impaired learning and memory loss (Sakata et al 2000, Naghdi et al 2005, Sandstrom et al 2006, Pintana et al 2015b). Consistent with the findings from testosterone deprivation, a number of studies also reported that ovariectomy-induced estrogen deficiency also led to peripheral insulin resistance and cognitive decline (Daniel et al 1997, Luine et al 1998, Pratchayasakul et al 2015.…”
Section: Introductionmentioning
confidence: 99%